Ocorrência e caracterização molecular de Cryptosporidium spp. em caprinos jovens do município de Quixadá-Ceará - Brito, Roberta Lomonte Lemos de [UNESP] (2014)
The present study aimed to evaluate the occurrence of infection and perform molecular characterization of Cryptosporidium spp. in goats kids from the town of Quixadá – state of Ceará – Brazil. A total of 400 animals, 154 males and 246 females, with aged between three and 360 days, with and without defined breed, from 25 farms distributed in three circuits, participated in this study. Stool samples were obtained directly from the goats rectum and registered in accordance to their appearance and coloring. An amount of 200 mg of each sample, were distributed in micro tubes of 2 mL and frozen “in nature” at -20 °C until the moment of extraction of the parasite genomic DNA using a commercial kit. All samples were submitted to Nested-PCR to amplify fragments of 18S subunit of ribosomal RNA. The positives samples in this amplification were tested in Nested-PCR with actin and HSP 70 genes. Samples that were amplified in these three genes were subjected to Nested-PCR triplicate and subjected to sequencing in sense and anti-sense directions. The occurrence of the infection by Cryptosporidium in goats kids of the town of Quixadá was 7.50% (30/400) and 64.00% (16/25) of the farms with positive goats. The Tapuiará district showed the highest number of positive animals and the frequency in dry and rainy period was 9.55% (19/199) and 5.47% (11/201), respectively (P = 0.1218). Considering 30 samples of positive stools, 50.00% (15/30) had normal appearance and 70.00% (21/30) normal coloring, suggesting that asymptomatic goats can eliminate oocysts in the environment. It was not observed positivity for Cryptosporidium spp. in animals aged between 301 and 360 days. Through sequencing, it was possible to identify that the species of coccidian found in the feces of the goats are Cryptosporidium xiaoi, Cryptosporidium ubiquitum and Cryptosporidium meleagridis. Different species of protozoa are present in rural farms ...